Pertanggungjawaban Hukum Ayah Terhadap Anak Setelah Terjadinya Perceraian - Barzah Latupono (Faculty of Law, Universitas Pattimura, 2020)
Every marriage that is done there ends until death separates, but there is also only a moment later divorced, divorce is a lot because the husband remarries without permission of the wife and obligations that the husband never did after divorcing his wife. After the termination of the marriage according to the law the husband and wife have the same duties and responsibilities in caring for and supporting their children. However, in reality, every woman who has been divorced by her husband will never again be supported by her husband again even though he has children children who also need money for their survival, and this father or ex-husband has never been sanctioned if he does not provide maintenance and education costs for his child, finally women often have to shoulder the burden of responsibility to the child whose parental rights belong to him.